2018
DOI: 10.1302/0301-620x.100b6.bjj-2017-1389.r1
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal screening and selective sonographic imaging in the diagnosis of developmental dysplasia of the hip

Abstract: Aims The aim of this prospective cohort study was to evaluate the effectiveness of the neonatal hip instability screening programme. Patients and Methods The study involved a four-year observational assessment of a neonatal hip screening programme. All newborns were examined using the Barlow or Ortolani manoeuvre within 72 hours of birth; those with positive findings were referred to a ‘one-stop’ screening clinic for clinical and sonographic assessment of the hip. The results were compared with previous publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 27 publications
(31 reference statements)
4
25
0
8
Order By: Relevance
“…We defined a positive clinical examination in the broadest pos- We recognise that including potential immature hips lowers the threshold for a true positive clinical examination in definition #1, which could explain why the PPV was higher than previous studies have found. 4 However, this highlights how differing definitions of pathological DDH results in varying rates of DDH diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We defined a positive clinical examination in the broadest pos- We recognise that including potential immature hips lowers the threshold for a true positive clinical examination in definition #1, which could explain why the PPV was higher than previous studies have found. 4 However, this highlights how differing definitions of pathological DDH results in varying rates of DDH diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The merits and disadvantages of universal and selective US examination are well documented in the literature,17–21 and there remains no clear consensus on the best model. What is agreed on however is the necessity of examination experience12–14 22 when electing for a programme of selective screening; centres which have reported low rates of late presentation all have a system of experienced examiners performing the initial neonatal examination.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability in the ultrasonography evaluation with Graf method of developmental dysplasia of the hip İ M L E R İ V E T I P D E R G İ S İ head coverage (FHC) at different positions corresponds to different reference values, and they stated Neutral and Flexion Positions (FHC-D) can be used as a quantitative indicator for assessment of hip stability (8). Choudry et al(9) founded the positive predictive value (PPV) of clinical screening was found as 4.0% and the PPV of sonography was found as 16.1%. They evaluated previously published 10 or 15-year studies, and they found a deterioration in the PPV in those with potential instability of the hip.…”
mentioning
confidence: 99%